Management of Muhammadiyah Middle Schools in Sidoarjo during The Covid-19 Pandemic - Yani, Muhammad; Hanun, Nur Ravita; Setiyono, Wisnu Panggah (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
The assessment method used in this research is a qualitative approach. Data collection techniques used in this study were observation, interviews and FGD with ten informants, namely the Head of Muhammadiyah Middle School in Sidoarjo. The data analysis technique uses three steps in collecting research results, namely data reduction (data reduction), data presentation (data display), and drawing and testing conclusions or verification. The results of this study are as follows: The school anticipates students who do not have Learning From Home (BDR) support facilities, limited internet access and financial constraints by setting up tabs provided at school, these tabs can be used by students to do assignments. The strategies applied are very diverse, including: Allocating teacher supervision funds for other needs, providing motivation and stimulus so that teachers can deliver learning optimally, collaborating with filmmakers to make learning videos, holding MSG (Morning Spiritual Gathering) activities or referred to as Ngaji, Briefing, and Berinfaq, while also seeking donations for students to pay tuition fees. Implementation of short-term and long-term plans: looking for a learning format that can be maximized, trying to foster parental trust in the school, trying to build communication with students and parents through activities that support education, collaborating with parents so as to foster an understanding that shared responsibility, focus on learning that is important for students' self-development, and improve the technological capabilities of students and teachers to be able to innovate in each other's learning.